Dirac's æther in curved spacetime - OLIVEIRA,ALEXANDRE L. (2000)
Proca's equations for two types of fields in a Dirac's æther with electric conductivity sigma are solved exactly. The Proca electromagnetic fields are assumed with cylindrical symmetry. The background is a static, curved spacetime whose spatial section is homogeneous and has the topology of either the three-sphere S³ or the projective three-space P³. Simple relations between the range of Proca field lambda, the Universe radius R, the limit of photon rest mass mgamma and the conductivity sigma are written down.